Geographical convergence patterns in the distribution of Drosophila species in Nagaland, a sub-Himalayan hilly state of North-east India - Achumi, Bovito; Hegde, Shridhar N.; Lal, Pardeshi; Zevelou; Yenisetti, Sarat Chandra (Journal of the Bombay Natural History Society (JBNHS), 2014)
No Abstract.